Capital Market Imperfection, the Consumption Function, and the Effectiveness of Fiscal Policy - Heller, Walter Perrin; Starr, Ross M. (Quarterly Journal of Economics, 1979)
I. Income and consumption, 455.—II. Optimal consumption plans subject to borrowing constraint, 457.—III. Dependence of consumption on income in the short run: a consumption function, 460.—IV. Summary, 462.